2020
DOI: 10.1109/twc.2019.2959763
|View full text |Cite
|
Sign up to set email alerts
|

Fundamentals of Power Allocation Strategies for Downlink Multi-User NOMA With Target Rates

Abstract: For downlink multi-user non-orthogonal multiple access (NOMA) systems with successive interference cancellation (SIC) receivers, and a base-station not possessing the instantaneous channel gains, the fundamental relationship between the target rates and power allocation is investigated. It is proven that the total interference from signals not removed by SIC has a fundamental upper limit which is a function of the target rates, and the outage probability is one when exceeding this limit. The concept of well-be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In the same channel, when a user with a smaller channel gain decodes the signal, the signal of a user whose channel gain is larger than itself is regarded as interference [39], so the signal-to-interference ratio (SINR) of U E n in the sub-channel s can be expressed as (3).…”
Section: Wireless Channel Modelmentioning
confidence: 99%
“…In the same channel, when a user with a smaller channel gain decodes the signal, the signal of a user whose channel gain is larger than itself is regarded as interference [39], so the signal-to-interference ratio (SINR) of U E n in the sub-channel s can be expressed as (3).…”
Section: Wireless Channel Modelmentioning
confidence: 99%
“…Indeed, this scattering causes a nondetectable constellation and a conceptual flaw in downlink NOMA schemes. Therefore, the power allocation (PA) constraint becomes too strict in practical scenarios and, contrary to PA optimization studies in terms of various constraints [40]- [43], no device can detect symbols if this strict PA constraint is not satisfied. In [31], it was shown that the PA of one of the users should be higher than 0.9 even in a case involving two users with 16-QAM.…”
Section: A Related Work and Motivationmentioning
confidence: 99%
“…2) Power Allocation Constraint: In the literature, great efforts have been devoted to optimizing the PA coefficient under different constraints, such as sum-rate maximization, outage probability, energy efficiency, etc., [40]- [43]. To the best of the authors' knowledge, all of the aforementioned studies optimize PA by considering the theoretical Shannon limit, and no transceiver (i.e., baseband signal processing) is considered.…”
Section: Multiaccessmentioning
confidence: 99%
“…Energy efficient based SIC decoding order with improved performance of outage probability in [2]. Thereafter, a new scheme for user admission through threshold difference based is explained in [3], and in resource block [4] contains all the related parameters like subcarriers, time slots and spreading codes with 5G requirements.…”
Section: Related Work On Nomamentioning
confidence: 99%